The relationship between strategic performance measurement systems and organisational competitive advantage / Rapiah Mohamed …[et al.] - Mohamed, Rapiah; Wee, Shu Hui; Abdul Rahman, Ibrahim Kamal; Abdul Aziz, Rozainun (Universiti Teknologi MARA Cawangan Selangor, 2010)
The main objective of this study is to examine the role of strategic performance measurement systems (SPMS) as a strategic control tool in assisting managers to enhance organisational competitive advantage. Specifically, the objective of this paper is to examine the extent to which organizations are adopting financial and non-financial measures and to determine the effect of SPMS design on organisational competitive advantage. The main research question of this study is - Does the adoption of SPMS that consists of financial and nonfinancial measures lead to enhanced organisation competitive advantage? This paper reports on the results of SPMS design and competitive advantage. The data was collected using a mail survey to top management of listed companies in Malaysia. The results indicate that the Malaysian companies in the sample adopted both financial and nonfinancial measures. The study also found that the relationship between SPMS design and competitive advantage was positive and significant. However, for the relationship of each dimension of SPMS and competitive advantage, only non-financial measures had a significant association with competitive advantage, while financial measures had an insignificant positive contribution to competitive advantage.